Misogyy As Violence In Gender Perspective - Ni Nyoman Juwita Arsawati; Dewi Bunga (Research Collaboration Community (RCC), 2022)
Misogyny is the behavior of someone hating women, both from men and fellow women. This behavior often places and views women as the cause of blame in a problem, even for something that is not really a problem. Misogyny causes a person tends to hate, look down on, blame, label and discriminate against women. This behavior is often associated with male privilege, patriarchal customs, and gender discrimination. In practice, this behavior will place men in a superior position, while women in an inferior position. In certain cases, misogynism can even increase the risk of physical, psychological and sexual harassment of women. There are two problems discussed in this study: 1) misogyny in the perspective of gender-based violence and 2) the relationship between misogyny and violence against women. This research is normative juridical research supported by empirical data on gender-based violence against women. Primary and secondary legal materials were collected through literature study. The research approach used is the statutory regulation, the legal concept, and the legal argumentation approach. Analysis of the collected data was carried out qualitatively.